Desenvolvimento do processo de produção de concentrado de enzimas xilanase e β-glicosidade na hidrólise de resíduos de mandioca - PASSOS, Letícia Cardoso dos (2019)
Extracellular enzymes are macromolecules that have biocatalyst function and are secreted by microorganisms that currently have great industrial applicability, especially in the hydrolysis of industrial waste. According to the literature, filamentous fungi have a high capacity of production of the enzymes present in which hydrolytic activities. Thus, the objective was to select strains of fungi have high potential for production of concentrates of xylanase and β-glucosidase capable of hydrolyzing residues rich in cellulose and hemicellulose. The strains selected were activated and induced to produce the enzymes studied in semisolid medium. After completion of the screening tests for enzymes studied, we evaluated the lines selected by submerged cultivation for a period of 240 hours and the production of concentrates by the strains of greatest potential for production for 16 days in agitation and static mode. In short, the initial evaluation in submerged cultures showed that fungal strains MIBA 0300, MIBA MIBA 0346 and 0769 highlights offered in the production of β-glucosidase and xylanase. Thus, the production of concentrates of β-glucosidase had higher activity at 3,9 U/mL for strain 0300 MIBA the stirring and the inhibition of the activity observed in static culture. In assessing the xylanase enzyme, there was increased activity of 3,000 U/mL and 2,750 U/ mL for MIBA 0769 and 0346 respectively in which were kept under stirring. From the data obtained it can be concluded that concentrates obtained have great ability to hydrolyze hemicellulolytic and cellulolytic materials contained in the wood xylan and wheat bran, respectively, and great possibilities of hydrolyzing amylaceous substances waste materials, such as cassava.